The Impacts of Ocean Acidification on Marine Food Quality and Its Potential Food Chain Consequences - Jin, Peng; Hutchins, David A.; Gao, Kunshan (Frontiers in Marine Science, 2020)
Dissolution of anthropogenic CO2 into the oceans results in ocean acidification (OA), altering marine chemistry with consequences for food web primary, secondary and tertiary producers. Here we examine how OA could affect the food quality of primary producers and subsequent trophic transfer to second and tertiary producers. Changes in food quality induced by OA are often related to secondary metabolites in primary producers, such as enriched phenolics in microalgae and iodine in brown algae. These biomolecules can then be transferred to secondary producers, potentially affecting seafood quality and other marine ecosystem services. Furthermore, shifts in dominant functional groups of primary producers under the influence of OA would also impact higher trophic levels through food web interactions. It is challenging to understand how these complex food chain effects of OA may be expressed under the influence of fluctuating environments or multiple drivers, and how these effects can be scaled up through marine food webs to humans.